‘A bed should be a haven’ : using poetry workshops to understand sleep in later life : a thesis presented in partial fulfilment of the requirements for the degree of Master of Health Science (Psychology) in College of Health at Massey University, Auckland, New Zealand - Knowles, Georgia Jessie (Massey University, 2025)
Sleep quality reportedly declines with ageing and sleep disorders increasingly impact wellbeing. Discourses of health promotion, such as those disseminated in the media, play a role in shaping perceptions and practices of sleep across the lifespan. However, such messaging is often negative, contradictory, and sensationalised. This project examined older people’s experiences of sleep, understandings of sleep health messaging, and provided a platform for sharing sleep-related experiences through poetry. Three sessions were conducted with 41 older people across Wellington (75% female, mean age 81 years). The sessions included focus groups on sleep and media messaging, followed by poetry workshops. Participants were invited to explore sleep in older age by writing poetry on their ‘best sleep’ and what a bed ‘should be’. Transcripts and poems were analysed using thematic analysis in three sections considering the shared understandings generated in the group discussion, the participants’ interpretations and negotiations of contemporary media messaging about sleep, and the deeper experiential insights expressed through their poetry. Participants discussed their subjective experiences of sleep for physical, emotional, and mental restoration, amongst the many challenges of sleep-in later life. They spoke of their resistance to confronting, fearful, and condescending sleep-related media messages, and their hesitance to trust, accept, and engage with them. Poems produced an idealised version of sleep, with the place and security of sleep as key features, alongside their perceptions of sleep beyond its physiological functions. Together, themes provided an alternative representation of sleep-in later life as more positive and nuanced. Findings advance understandings of how older people consume, interpret, and respond to media messages on sleep. Using creative methods, this work provided opportunities for sharing experiences, beliefs, and practices in relation to sleep in later life. These findings highlight the need for future research that examines sleep in later life across more diverse cultural, socioeconomic, and health contexts, including older adults living with chronic illness or sleep disorders, in order to deepen understanding of how ageing, embodiment, and social environments shape sleep experiences.
Figure 1 is reused with permission.
Keywords: 420101 Arts therapy; 520106 Psychology of ageing